Alcohol packaging material with slow release performance

By adding light calcium carbonate and elotite nanotube/nanotitanium dioxide composite to the polyethylene sustained-release layer of alcohol packaging material and applying a sustained-release outer coating on the surface, the problem of insufficient mechanical properties of existing materials is solved, and the alcohol sustained-release and antibacterial properties are improved, and the shelf life of food is extended.

CN119708590APending Publication Date: 2025-03-28JIAXING LUCKY MOON PACKAGING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510026780.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing alcohol packaging materials with sustained release properties are low in mechanical properties and are difficult to maintain integrity and sealing during transportation and storage, resulting in alcohol volatility and leakage.

Method used

Linear low-density polyethylene is used as the main matrix material, and light calcium carbonate and Elosite nanotube/nanotitanium dioxide composite are added to modify the polyethylene sustained release layer. At the same time, the polyethylene sustained-release layer is coated with a sustained-release outer coating composed of chitosan, eloite nanotube/nanotitanium dioxide composite and sodium carboxymethylcellulose.

Benefits of technology

It improves the strength and toughness of the polyethylene sustained-release layer, enhances its stability and durability, ensures the sustained-release performance of alcohol, and improves the antibacterial properties of packaging materials, extends the storage period or shelf life of food.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of packaging materials, in particular to an alcohol packaging material with slow-release performance, which comprises a polyethylene slow-release layer and a slow-release outer coating coated on the polyethylene slow-release layer, the polyethylene slow-release layer is prepared from the following raw materials: linear low-density polyethylene, maleic anhydride grafted polyethylene, a polyolefin elastomer, a silane coupling agent, light calcium carbonate and a halloysite nanotube / nano titanium dioxide composite material; the slow-release outer coating is prepared from the following raw materials: a chitosan solution, a halloysite nanotube / nano titanium dioxide composite material and sodium carboxymethyl cellulose. The alcohol packaging material provided by the invention not only shows excellent and stable alcohol slow-release performance, but also has good mechanical properties, also shows good antibacterial performance, and is matched with slow-release alcohol to further improve the fresh-keeping effect on food.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of packaging materials, and in particular to an alcohol packaging material with sustained-release performance. Background Art

[0002] At present, in order to extend the storage period or shelf life of some foods, low-temperature storage and chemical treatment are generally used. However, low-temperature storage consumes a lot of energy and has high equipment costs. Although chemical treatment is convenient and low-cost, chemical agents will remain in the food, causing food safety problems. Therefore, the development of simple, efficient, safe and low-cost food preservation methods is of great significance to extend the storage period or shelf life of food.

[0003] Since ethanol has a high bactericidal ability, it can effectively inhibit the growth and reproduction of bacteria, fungi and viruses, so ethanol can prevent food from corruption and deterioration. At the same time, ethanol can be quickly mixed with water to form a low water activity environment, so that microorganisms cannot survive and reproduce. And for some vegetables, fruits and other foods, ethanol can suppress its respiration rate, and then can achieve the preservation of vegetables and fruits. Therefore, the material loaded with alcohol is packaged with a packaging material with slow-release performance, so that alcohol is slowly released in the storage environment of food, which can effectively extend the storage period or shelf life of food.

[0004] For the current alcohol packaging materials with sustained-release properties, they are generally made of polyethylene materials. Although the current polyethylene has good chemical stability and barrier properties, its mechanical properties are relatively low. If it is subjected to large external forces such as squeezing, collision, pulling, etc. during transportation and storage, it may be damaged. As an alcohol packaging material with sustained-release properties, it is necessary to ensure that the integrity and sealing of the packaging are maintained for a long time to prevent alcohol from volatilizing and leaking. Therefore, it is necessary to develop and modify the polyethylene packaging material used to prepare sustained-release alcohol so that it can maintain excellent and stable alcohol sustained-release properties while also having excellent mechanical properties to prevent alcohol from volatilizing and leaking. Summary of the invention

[0005] The purpose of the present invention is to provide an alcohol packaging material with sustained-release properties. The alcohol packaging material not only exhibits excellent and stable alcohol sustained-release properties, but also has good mechanical properties and good antibacterial properties. When combined with the sustained-release alcohol, the food preservation effect is further improved.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: An alcohol packaging material with sustained-release performance, the alcohol packaging material comprising a polyethylene sustained-release layer and a sustained-release outer coating coated on the polyethylene sustained-release layer; The polyethylene sustained-release layer comprises the following raw materials: linear low-density polyethylene, maleic anhydride grafted polyethylene, polyolefin elastomer, silane coupling agent, light calcium carbonate, and halloysite nanotube / nano-titanium dioxide composite material; The sustained-release outer coating comprises the following raw materials: chitosan solution, halloysite nanotube / nano-titanium dioxide composite material, and sodium carboxymethyl cellulose.

[0007] Preferably, the polyethylene sustained-release layer comprises the following raw materials in parts by weight: 100 parts of linear low-density polyethylene, 7-15 parts of maleic anhydride grafted polyethylene, 3-7 parts of polyolefin elastomer, 0.3-0.5 parts of silane coupling agent, 15-20 parts of light calcium carbonate, and 2.5-5 parts of halloysite nanotube / nano-titanium dioxide composite material. In the present invention, the addition amount of maleic anhydride grafted polyethylene, polyolefin elastomer, and halloysite nanotube / nano-titanium dioxide composite material is mainly appropriate. If too little is added, the expected modification effect cannot be achieved, and if too much is added, the alcohol sustained-release ability of the polyethylene sustained-release layer will be reduced.

[0008] Preferably, the sustained-release outer coating comprises the following raw materials in parts by weight: 100 parts of chitosan solution, 0.05-0.1 parts of halloysite nanotube / nano-titanium dioxide composite material, and 1-1.5 parts of sodium carboxymethyl cellulose; the mass fraction of the chitosan solution is 2.5-3.5%.

[0009] Preferably, the thickness of the polyethylene sustained-release layer is 35-45 μm; the thickness of the sustained-release outer coating is 3-6 μm.

[0010] Preferably, the silane coupling agent is at least one of KH550 and KH560; the silane coupling agent is used to modify the halloysite nanotube / nano-titanium dioxide composite material, enhance the dispersibility of the composite material in the polyethylene sustained-release layer and the binding force between the composite material and the polymer, and better play the modification effect of the halloysite nanotube / nano-titanium dioxide composite material.

[0011] The polyolefin elastomer is at least one of ethylene-butene copolymer and ethylene-octene copolymer.

[0012] Preferably, the preparation method of the halloysite nanotube / nano-titanium dioxide composite material comprises the following steps: 100 parts of ethanol, 5 to 10 parts of deionized water and 12 to 15 parts of acetic acid are added to a reaction kettle to obtain a mixed solution; 6 to 10 parts of halloysite nanotubes are added to the mixed solution, and then 5 to 10 parts of a 10 to 15% by mass tetrabutyl titanate ethanol solution are added dropwise while stirring, and after the addition, the reaction kettle is closed, the temperature is increased for a hydrothermal reaction, and then the mixture is cooled, filtered, washed with water and vacuum dried in sequence; and the obtained material is calcined under a nitrogen atmosphere to obtain the halloysite nanotube / nano-titanium dioxide composite material.

[0013] Preferably, the temperature of the hydrothermal reaction is 135-150° C., and the time is 5-7.5 h; the temperature of the calcination is 400-460° C., and the time is 1-2 h.

[0014] Preferably, the method for preparing the polyethylene sustained-release layer comprises the following steps: S1: Light calcium carbonate, halloysite nanotube / nano-titanium dioxide composite material and silane coupling agent are placed in a high-speed mixer and mixed evenly, and then the obtained material is mixed evenly with linear low-density polyethylene, maleic anhydride grafted polyethylene and polyolefin elastomer, and granulated by a twin-screw extruder to obtain a masterbatch; and then the obtained masterbatch is put into a casting machine for casting to obtain a polyethylene sustained-release film; S2: treating the surface of the polyethylene sustained-release film with oxygen plasma to obtain a polyethylene sustained-release layer.

[0015] Preferably, when the oxygen plasma treatment is performed, the treatment power is 100-150 W and the treatment time is 3-5 min. By modifying the polyethylene sustained-release film with oxygen plasma, the surface of the polyethylene sustained-release film has more active sites and higher roughness, thereby making it more strongly bonded to the sustained-release outer coating.

[0016] Preferably, the method for preparing the alcohol packaging material comprises the following steps: 1) adding chitosan to an aqueous solution of acetic acid having a mass fraction of 2.5-3%, stirring and dissolving, thereby preparing the chitosan solution; 2) adding sodium carboxymethyl cellulose and halloysite nanotube / nano-titanium dioxide composite material to the chitosan solution, stirring and mixing for 0.5 to 1 hour, and then ultrasonically dispersing for 1 to 2 hours while stirring to prepare a mixed coating; 3) coating the mixed coating on the polyethylene slow-release layer, and drying the coating to form a slow-release outer coating on the surface of the polyethylene slow-release layer, thereby obtaining the alcohol packaging material with slow-release performance.

[0017] The beneficial effects of the present invention are: When preparing the polyethylene sustained-release layer of the alcohol packaging material, the present invention selects linear low-density polyethylene as the main matrix material, and adds a suitable amount of light calcium carbonate. On this basis, the polyethylene sustained-release layer is modified by using a halloysite nanotube / nano-titanium dioxide composite material. On the one hand, since the halloysite nanotube can form physical crosslinking points with the molecular chains of the polymer, it can be stably connected to the polyethylene sustained-release layer, thereby effectively improving the strength and toughness of the polyethylene sustained-release layer, and enhancing the stability and durability of the polyethylene sustained-release layer; on the other hand, through the composite of the halloysite nanotube and the nano-titanium dioxide, the nano-titanium dioxide can be highly dispersed in the polyethylene sustained-release layer, and the highly dispersed nano-titanium dioxide can show a higher antibacterial effect, so that the alcohol packaging material itself can enhance its antibacterial performance for the food storage environment, thereby improving the preservation effect.

[0018] In addition, the present invention adopts a mixture of linear low-density polyethylene, maleic anhydride grafted polyethylene and polyolefin elastomer as the polymer matrix material, which can improve the compatibility of the polymer matrix with the halloysite nanotube / nano-titanium dioxide composite material, while also improving the overall mechanical properties of the polymer matrix, including strength, toughness, etc., and improving the processing performance.

[0019] The present invention is based on the polyethylene sustained-release layer, and a sustained-release outer coating is coated on the surface thereof. The stable sustained-release film layer can be formed by combining chitosan, sodium carboxymethyl cellulose, and halloysite nanotube / nano-titanium dioxide composite material. The sustained-release film layer can be combined with the polyethylene sustained-release layer to better control the sustained-release rate of alcohol, making the sustained-release rate more stable, and it has a certain strength, so that the overall structure of the packaging material can be more stable. In view of the fact that the chitosan and halloysite nanotube / nano-titanium dioxide composite material have higher antibacterial properties, the sustained-release outer coating exhibits excellent antibacterial properties.

[0020] By combining the polyethylene sustained-release layer with the sustained-release outer coating, and each layer is prepared using preferred raw materials, the resulting alcohol packaging material not only exhibits excellent and stable alcohol sustained-release performance, but also has good mechanical properties and itself exhibits good antibacterial properties. Together with the sustained-release alcohol, it further enhances the food preservation effect. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] In the following examples and comparative examples, the brand of the linear low-density polyethylene used is ExxonMobil, with the brand name LL 6101XR; the brand of the ethylene-butene copolymer is ExxonMobil, with the brand name 9071; and the brand of the maleic anhydride grafted polyethylene is Arkema, with the brand name OE850.

[0023] Embodiment 1: An alcohol packaging material with sustained-release performance comprises a polyethylene sustained-release layer and a sustained-release outer coating coated on the polyethylene sustained-release layer.

[0024] The polyethylene sustained-release layer comprises the following raw materials in parts by weight: 100 parts of linear low-density polyethylene, 10 parts of maleic anhydride grafted polyethylene, 5 parts of ethylene-butene copolymer, 0.3 parts of silane coupling agent KH550, 15 parts of light calcium carbonate, and 4 parts of halloysite nanotube / nano-titanium dioxide composite material.

[0025] The sustained-release outer coating layer comprises the following raw materials in parts by weight: 100 parts of chitosan solution with a mass fraction of 3.5%, 0.1 parts of halloysite nanotube / nano-titanium dioxide composite material, and 1 part of sodium carboxymethyl cellulose.

[0026] The preparation method of the above-mentioned halloysite nanotube / nano-titanium dioxide composite material comprises the following steps: Add 100 parts of ethanol, 10 parts of deionized water and 12 parts of acetic acid into a reactor to obtain a mixed solution; add 8 parts of halloysite nanotubes into the mixed solution, then dropwise add 9 parts of 10% by mass tetrabutyl titanate ethanol solution while stirring, close the reactor after the dropwise addition, and heat up to perform a hydrothermal reaction at a temperature of 135° C. for 6.5 hours; then cool, filter, wash with water and vacuum dry in sequence; and then calcine the obtained material under a nitrogen atmosphere at a temperature of 420° C. for 2 hours to obtain a halloysite nanotube / nano-titanium dioxide composite material.

[0027] The preparation method of the alcohol packaging material with sustained-release performance in this embodiment comprises the following steps: S1: Light calcium carbonate, halloysite nanotube / nano-titanium dioxide composite material and silane coupling agent KH550 are placed in a high-speed mixer and mixed evenly, and then the obtained material is mixed evenly with linear low-density polyethylene, maleic anhydride grafted polyethylene and ethylene-butene copolymer, and granulated by a twin-screw extruder to obtain a masterbatch; the extrusion temperature is divided into 4 zones, the first temperature zone is 150°C, the second temperature zone is 165°C, the third temperature zone is 175°C, and the fourth temperature zone is 185°C; Then the obtained masterbatch is put into a casting machine for casting into a film to obtain a polyethylene sustained-release film; S2: treating the surface of the polyethylene sustained-release film with oxygen plasma at a treatment power of 150 W for 5 min to obtain a polyethylene sustained-release layer; S3: adding chitosan to an aqueous solution of acetic acid having a mass fraction of 3%, stirring and dissolving, to prepare the chitosan solution; adding sodium carboxymethyl cellulose and halloysite nanotube / nano-titanium dioxide composite material to the chitosan solution, stirring and mixing for 1 hour, and then ultrasonically dispersing while stirring for 1 hour to prepare a mixed coating; S4: coating the mixed coating on the polyethylene sustained-release layer, and drying the coating to form a sustained-release outer coating on the surface of the polyethylene sustained-release layer, thereby obtaining the alcohol packaging material with sustained-release performance.

[0028] Embodiment 2: An alcohol packaging material with sustained-release performance comprises a polyethylene sustained-release layer and a sustained-release outer coating coated on the polyethylene sustained-release layer.

[0029] The polyethylene sustained-release layer comprises the following raw materials in parts by weight: 100 parts of linear low-density polyethylene, 7 parts of maleic anhydride grafted polyethylene, 7 parts of ethylene-butene copolymer, 0.4 parts of silane coupling agent KH560, 17 parts of light calcium carbonate, and 5 parts of halloysite nanotube / nano-titanium dioxide composite material.

[0030] The sustained-release outer coating layer comprises the following raw materials in parts by weight: 100 parts of chitosan solution with a mass fraction of 2.5%, 0.08 parts of halloysite nanotube / nano-titanium dioxide composite material, and 1.5 parts of sodium carboxymethyl cellulose.

[0031] The preparation method of the above-mentioned halloysite nanotube / nano-titanium dioxide composite material comprises the following steps: Add 100 parts of ethanol, 7 parts of deionized water and 12 parts of acetic acid into a reactor to obtain a mixed solution; add 10 parts of halloysite nanotubes into the mixed solution, and then drop 10 parts of 10% by mass tetrabutyl titanate ethanol solution while stirring, close the reactor after the dropwise addition, and heat it up for hydrothermal reaction at a temperature of 150° C. for 7.5 hours; then cool, filter, wash with water and vacuum dry in sequence; and then calcine the obtained material under a nitrogen atmosphere at a temperature of 460° C. for 1.5 hours to obtain a halloysite nanotube / nano-titanium dioxide composite material.

[0032] The preparation method of the alcohol packaging material with sustained-release performance in this embodiment comprises the following steps: S1: Light calcium carbonate, halloysite nanotube / nano-titanium dioxide composite material and silane coupling agent KH560 are placed in a high-speed mixer and mixed evenly, and then the obtained material is mixed evenly with linear low-density polyethylene, maleic anhydride grafted polyethylene and ethylene-butene copolymer, and granulated by a twin-screw extruder to obtain a masterbatch; the extrusion temperature is divided into 4 zones, the first temperature zone is 155°C, the second temperature zone is 170°C, the third temperature zone is 175°C, and the fourth temperature zone is 185°C; Then the obtained masterbatch is put into a casting machine for casting into a film to obtain a polyethylene sustained-release film; S2: treating the surface of the polyethylene sustained-release film with oxygen plasma at a treatment power of 100 W for 3 min to obtain a polyethylene sustained-release layer; S3: adding chitosan to an aqueous solution of acetic acid with a mass fraction of 2.5%, stirring and dissolving, to prepare the chitosan solution; adding sodium carboxymethyl cellulose and halloysite nanotube / nano-titanium dioxide composite material to the chitosan solution, stirring and mixing for 0.5 h, and then ultrasonically dispersing for 2 h while stirring, to prepare a mixed coating; S4: coating the mixed coating on the polyethylene sustained-release layer, and drying the coating to form a sustained-release outer coating on the surface of the polyethylene sustained-release layer, thereby obtaining the alcohol packaging material with sustained-release performance.

[0033] Embodiment 3: An alcohol packaging material with sustained-release performance comprises a polyethylene sustained-release layer and a sustained-release outer coating coated on the polyethylene sustained-release layer.

[0034] The polyethylene sustained-release layer comprises the following raw materials in parts by weight: 100 parts of linear low-density polyethylene, 15 parts of maleic anhydride grafted polyethylene, 3 parts of ethylene-butene copolymer, 0.3 parts of silane coupling agent KH550, 17 parts of light calcium carbonate, and 2.5 parts of halloysite nanotube / nano-titanium dioxide composite material.

[0035] The sustained-release outer coating layer comprises the following raw materials in parts by weight: 100 parts of chitosan solution with a mass fraction of 3%, 0.05 parts of halloysite nanotube / nano-titanium dioxide composite material, and 1.2 parts of sodium carboxymethyl cellulose.

[0036] The preparation method of the above-mentioned halloysite nanotube / nano-titanium dioxide composite material comprises the following steps: 100 parts of ethanol, 5 parts of deionized water and 15 parts of acetic acid are added to a reactor to obtain a mixed solution; 6 parts of halloysite nanotubes are added to the mixed solution, and then 5 parts of a 15% by mass tetrabutyl titanate ethanol solution are added dropwise while stirring, and after the addition is completed, the reactor is closed and the temperature is increased for a hydrothermal reaction at a temperature of 140° C. for 5 hours; then the mixture is cooled, filtered, washed with water and vacuum dried in sequence; and the obtained material is calcined in a nitrogen atmosphere at a temperature of 400° C. for 1 to 2 hours to obtain a halloysite nanotube / nano-titanium dioxide composite material.

[0037] The preparation method of the alcohol packaging material with sustained-release performance in this embodiment comprises the following steps: S1: Light calcium carbonate, halloysite nanotube / nano-titanium dioxide composite material and silane coupling agent KH550 are placed in a high-speed mixer and mixed evenly, and then the obtained material is mixed evenly with linear low-density polyethylene, maleic anhydride grafted polyethylene and ethylene-butene copolymer, and granulated by a twin-screw extruder to obtain a masterbatch; the extrusion temperature is divided into 4 zones, the first temperature zone is 150°C, the second temperature zone is 165°C, the third temperature zone is 175°C, and the fourth temperature zone is 185°C; Then the obtained masterbatch is put into a casting machine for casting into a film to obtain a polyethylene sustained-release film; S2: treating the surface of the polyethylene sustained-release film with oxygen plasma at a treatment power of 100 W for 5 min to obtain a polyethylene sustained-release layer; S3: adding chitosan to an aqueous solution of acetic acid with a mass fraction of 2.5%, stirring and dissolving, to prepare the chitosan solution; adding sodium carboxymethyl cellulose and halloysite nanotube / nano-titanium dioxide composite material to the chitosan solution, stirring and mixing for 1 hour, and then ultrasonically dispersing while stirring for 2 hours to prepare a mixed coating; S4: coating the mixed coating on the polyethylene sustained-release layer, and drying the coating to form a sustained-release outer coating on the surface of the polyethylene sustained-release layer, thereby obtaining the alcohol packaging material with sustained-release performance.

[0038] Embodiment 4: An alcohol packaging material with sustained-release performance comprises a polyethylene sustained-release layer and a sustained-release outer coating coated on the polyethylene sustained-release layer.

[0039] The polyethylene sustained-release layer comprises the following raw materials in parts by weight: 100 parts of linear low-density polyethylene, 10 parts of maleic anhydride grafted polyethylene, 5 parts of ethylene-butene copolymer, 0.3 parts of silane coupling agent KH550, 20 parts of light calcium carbonate, and 4.5 parts of halloysite nanotube / nano-titanium dioxide composite material.

[0040] The sustained-release outer coating layer comprises the following raw materials in parts by weight: 100 parts of chitosan solution with a mass fraction of 3%, 0.06 parts of halloysite nanotube / nano-titanium dioxide composite material, and 1.3 parts of sodium carboxymethyl cellulose.

[0041] The preparation method of the halloysite nanotube / nano-titanium dioxide composite material in this example is the same as that in Example 1.

[0042] The preparation method of the alcohol packaging material with sustained-release properties in this embodiment is the same as that in Example 1.

[0043] Embodiment 5: An alcohol packaging material with sustained-release performance comprises a polyethylene sustained-release layer and a sustained-release outer coating coated on the polyethylene sustained-release layer.

[0044] The polyethylene sustained-release layer comprises the following raw materials in parts by weight: 100 parts of linear low-density polyethylene, 9 parts of maleic anhydride grafted polyethylene, 6 parts of ethylene-butene copolymer, 0.4 parts of silane coupling agent KH560, 18 parts of light calcium carbonate, and 3.5 parts of halloysite nanotube / nano-titanium dioxide composite material.

[0045] The sustained-release outer coating layer comprises the following raw materials in parts by weight: 100 parts of chitosan solution with a mass fraction of 3.5%, 0.09 parts of halloysite nanotube / nano-titanium dioxide composite material, and 1.1 parts of sodium carboxymethyl cellulose.

[0046] The preparation method of the halloysite nanotube / nano-titanium dioxide composite material in this embodiment is the same as that in Example 2.

[0047] The preparation method of the alcohol packaging material with sustained-release properties in this example is the same as that in Example 3.

[0048] Embodiment 6: An alcohol packaging material with sustained-release performance comprises a polyethylene sustained-release layer and a sustained-release outer coating coated on the polyethylene sustained-release layer.

[0049] The polyethylene sustained-release layer comprises the following raw materials in parts by weight: 100 parts of linear low-density polyethylene, 12 parts of maleic anhydride grafted polyethylene, 4 parts of ethylene-butene copolymer, 0.5 parts of silane coupling agent KH550, 18 parts of light calcium carbonate, and 4.5 parts of halloysite nanotube / nano-titanium dioxide composite material.

[0050] The sustained-release outer coating layer comprises the following raw materials in parts by weight: 100 parts of chitosan solution with a mass fraction of 3%, 0.1 parts of halloysite nanotube / nano-titanium dioxide composite material, and 1.2 parts of sodium carboxymethyl cellulose.

[0051] The preparation method of the halloysite nanotube / nano-titanium dioxide composite material in this example is the same as that in Example 3.

[0052] The preparation method of the alcohol packaging material with sustained-release properties in this embodiment is the same as that in Example 2.

[0053] Comparative Example 1: The difference from Example 1 is that the halloysite nanotube / nano-titanium dioxide composite material in the polyethylene sustained-release layer and the sustained-release outer coating material is replaced by a mixture of halloysite nanotube and nano-titanium dioxide in a mass ratio of 15:1. Other raw materials and processes are basically the same as those in Example 1.

[0054] Comparative Example 2: Different from Example 1, the polyethylene sustained-release layer includes the following raw materials in parts by weight: 115 parts of linear low-density polyethylene, 0.3 parts of silane coupling agent KH550, 15 parts of light calcium carbonate, and 4 parts of halloysite nanotube / nano-titanium dioxide composite material. Other raw materials and processes are basically the same as those in Example 1.

[0055] Comparative Example 3: Different from Example 1, the polyethylene sustained-release layer includes the following raw materials in parts by weight: 100 parts of linear low-density polyethylene, 3 parts of maleic anhydride grafted polyethylene, 2 parts of polyolefin elastomer, 0.3 parts of silane coupling agent, 15 parts of light calcium carbonate, and 4 parts of halloysite nanotube / nano-titanium dioxide composite material.

[0056] Comparative Example 4: Different from Example 1, the polyethylene sustained-release layer includes the following raw materials in parts by weight: 100 parts of linear low-density polyethylene, 30 parts of maleic anhydride grafted polyethylene, 15 parts of polyolefin elastomer, 0.3 parts of silane coupling agent, 15 parts of light calcium carbonate, and 4 parts of halloysite nanotube / nano-titanium dioxide composite material.

[0057] test: 1. The tensile strength and elongation at break of the polyethylene sustained-release film materials prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were tested according to the method in GB / T1040.3-2006. The specific test results are shown in Table 1.

[0058] Table 1 Test results of tensile strength and elongation at break

[0059] As shown in Table 1, the polyethylene sustained-release film material prepared by the method of the present invention has high tensile strength and elongation at break, excellent mechanical properties, and is not easily damaged by external forces. By comparing Example 1 with Comparative Example 1, it can be seen that if the halloysite nanotube / nano-titania composite material is replaced with a mixture of halloysite nanotubes and nano-titania, the mechanical properties will be significantly reduced. By comparing Example 1 with Comparative Examples 2-4, it can be seen that when the polyethylene sustained-release layer does not contain maleic anhydride grafted polyethylene, ethylene-butene copolymer or the content of maleic anhydride grafted polyethylene and ethylene-butene copolymer is too little, the tensile strength and elongation at break of the polyethylene sustained-release film material will be reduced, and when the amount of maleic anhydride grafted polyethylene and ethylene-butene copolymer added is less than or equal to an excessive amount, the tensile strength and elongation at break do not change much.

[0060] 2. An alcohol packaging material was prepared by the method of Examples 1 to 6 of the present invention and Comparative Examples 1 to 4, wherein the thickness of the polyethylene sustained-release layer was 40 μm, and the thickness of the sustained-release outer coating was 5 μm. The material was prepared into a 5 cm×5 cm sealed bag, and then filled with diatomaceous earth that had absorbed alcohol to near saturation, with 8 g of the diatomaceous earth that had absorbed alcohol being loaded into each sealed bag to obtain an alcohol sustained-release bag.

[0061] Fresh Kyoho grapes were sealed in polyethylene bags (35×25cm) and placed in alcohol slow-release bags. They were stored at 15-20℃ in dark conditions for 7 days. The ethanol solubility was measured every 24 hours during the storage period. Each test was conducted twice and the average of the test values ​​was taken as the result.

[0062] Test method for ethanol concentration: Use a syringe to extract 1 mL of gas from a polyethylene fresh-keeping bag and inject it into a gas chromatograph. Use standard ethanol gas as a control to measure the ethanol concentration in the bag.

[0063] In addition to testing the ethanol concentration, the rot rate of the grapes was also calculated.

[0064] Table 2 Ethanol solubility and decay rate test results

[0065] As shown in Table 2, the alcohol packaging materials in Examples 1 to 6 and Comparative Examples 1 to 3 all have good alcohol sustained-release properties, good grape preservation effects, and low rot rates. As shown in Comparative Example 4, if too much maleic anhydride grafted polyethylene or polyolefin elastomer is added, the ethanol sustained-release capacity of the alcohol packaging material will be reduced, the amount of sustained-released alcohol will be small, and the rot rate of the grapes will be significantly increased.

[0066] 3. The alcohol packaging materials prepared by the methods in Examples 1 to 6 and Comparative Examples 1 to 4 were tested for antibacterial properties according to the method in QB / T 2591-2003. The specific test results are shown in Table 3.

[0067] Table 3 Antibacterial performance test results

[0068] It can be seen from Table 3 that the alcohol packaging materials in Examples 1 to 6 and Comparative Examples 2 to 4 have good antibacterial properties, and the sustained-release outer coating of the present invention can show a good antibacterial effect. By comparing Comparative Example 1 with Example 1, it can be seen that the antibacterial property of the alcohol packaging material in Comparative Example 1 is reduced.

[0069] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An alcohol packaging material with sustained-release properties, characterized in that: The alcohol packaging material comprises a polyethylene sustained-release layer and a sustained-release outer coating coated on the polyethylene sustained-release layer; The polyethylene sustained-release layer comprises the following raw materials: linear low-density polyethylene, maleic anhydride grafted polyethylene, polyolefin elastomer, silane coupling agent, light calcium carbonate, and halloysite nanotube / nano-titanium dioxide composite material; The sustained-release outer coating comprises the following raw materials: chitosan solution, halloysite nanotube / nano-titanium dioxide composite material, and sodium carboxymethyl cellulose.

2. The alcohol packaging material with sustained release performance according to claim 1, characterized in that: The polyethylene sustained-release layer comprises the following raw materials in parts by weight: 100 parts of linear low-density polyethylene, 7-15 parts of maleic anhydride grafted polyethylene, 3-7 parts of polyolefin elastomer, 0.3-0.5 parts of silane coupling agent, 15-20 parts of light calcium carbonate, and 2.5-5 parts of halloysite nanotube / nano-titanium dioxide composite material.

3. The alcohol packaging material with sustained release performance according to claim 1, characterized in that: The sustained-release outer coating comprises the following raw materials in parts by weight: 100 parts of chitosan solution, 0.05-0.1 parts of halloysite nanotube / nano-titanium dioxide composite material, and 1-1.5 parts of sodium carboxymethyl cellulose; The mass fraction of the chitosan solution is 2.5-3.5%.

4. The alcohol packaging material with sustained release performance according to claim 1, characterized in that: The thickness of the polyethylene sustained-release layer is 35-45 μm; the thickness of the sustained-release outer coating is 3-6 μm.

5. The alcohol packaging material with sustained release performance according to claim 1, characterized in that: The silane coupling agent is at least one of KH550 and KH560; the polyolefin elastomer is at least one of ethylene-butene copolymer and ethylene-octene copolymer.

6. The alcohol packaging material with sustained release performance according to any one of claims 1 to 5, characterized in that: The preparation method of the halloysite nanotube / nano-titanium dioxide composite material comprises the following steps: 100 parts of ethanol, 5 to 10 parts of deionized water and 12 to 15 parts of acetic acid are added to a reaction kettle to obtain a mixed solution; 6 to 10 parts of halloysite nanotubes are added to the mixed solution, and then 5 to 10 parts of a 10 to 15% by mass tetrabutyl titanate ethanol solution are added dropwise while stirring, and after the addition, the reaction kettle is closed, the temperature is increased for a hydrothermal reaction, and then the mixture is cooled, filtered, washed with water and vacuum dried in sequence; and the obtained material is calcined under a nitrogen atmosphere to obtain the halloysite nanotube / nano-titanium dioxide composite material.

7. The alcohol packaging material with sustained release performance according to claim 6, characterized in that: The temperature of the hydrothermal reaction is 135-150° C., and the time is 5-7.5 hours; the temperature of the calcination is 400-460° C., and the time is 1-2 hours.

8. The alcohol packaging material with sustained release performance according to any one of claims 1 to 5, characterized in that: The preparation method of the polyethylene sustained-release layer comprises the following steps: S1: The halloysite nanotube / nano-titanium dioxide composite material, light calcium carbonate and silane coupling agent are placed in a high-speed mixer and mixed evenly, and then the obtained material is mixed evenly with linear low-density polyethylene, maleic anhydride grafted polyethylene and polyolefin elastomer, and granulated by a twin-screw extruder to obtain a masterbatch; and then the obtained masterbatch is put into a casting machine for casting to obtain a polyethylene sustained-release film; S2: treating the surface of the polyethylene sustained-release film with oxygen plasma to obtain a polyethylene sustained-release layer.

9. The alcohol packaging material with sustained release performance according to any one of claims 1 to 5, characterized in that: During the oxygen plasma treatment, when the treatment power is 100-150W, the treatment time is 3-5min.

10. The alcohol packaging material with sustained release performance according to claim 9, characterized in that: The preparation method of the alcohol packaging material comprises the following steps: Adding chitosan to an acetic acid aqueous solution having a mass fraction of 2.5-3%, stirring and dissolving, to prepare the chitosan solution; Adding sodium carboxymethyl cellulose and halloysite nanotube / nano-titanium dioxide composite material to the chitosan solution, stirring and mixing for 0.5 to 1 hour, and then ultrasonically dispersing for 1 to 2 hours while stirring to prepare a mixed coating; The mixed coating is coated on the polyethylene slow-release layer and dried after coating to form a slow-release outer coating on the surface of the polyethylene slow-release layer, thereby obtaining the alcohol packaging material with slow-release performance.